Pengelolaan Pemesanan Menu Makanan Menggunakan Framework Flask Python - muhammad Sholeh; Wisnu Laksita Aji; Yudhistira Riady; Brilly Lutfan Qasthari (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The development of information technology has an impact on changes in services in all sectors. Services that have been using concepts in paper form have changed to using information technology-based applications. The use of paper must be abandoned and replaced by application-based services. Likewise, the food menu list service in a restaurant no longer uses paper but can be developed using an application-based menu service. This research aims to create an information system application that can serve food menus in website-based restaurants. The application was developed using the flask Python framework and using the Mysql database management system. The research method uses the waterfall system development model. Model development begins with system analysis, system design, database design and coding and evaluation. The process of modeling the system using the Unified Modeling Language (UML). The results of the study resulted in a website-based food menu service application. The developed application is divided into two parts, namely the front end and the back end. The application on the front end is an application that will be used by customers who will choose the food menu and make the ordering process. This application can display a list of food menus and store data related to the food menu ordered by the user. Another application developed is a back end application. Applications on the back end perform data management by the administrator. In this section the application focuses more on data maintenance. With this application-based food menu service application, the service no longer uses paper menus and the ordering process can be done quickly. From the user's side, with this application service, they can directly select the menu in the application and immediately get information on the cost of ordering food.